The Role of Parents In Learning Spirit Early Childhood - Krisda; Sumi'ah; Ananta, Violin; Kurniawa, Wahyu (International Journal of Education and Teaching Zone, 2023)
The research entitled "The Role of Parents in Early Childhood Learning Enthusiasm" aims to discover how important parents' role is in seeing their children and educating their children to be passionate about learning. This type of research is qualitative research. The subjects of this study were parents and students of AWWABIEN Kindergarten in Jambi City for the 2022/2023 academic year, totalling 34 students, 18 boys and 16 girls. The data collection technique used was interviews with teachers, students and parents. The data analysis technique used is to analyze the instruments that have been given. The results of this study are parents who have the most role in the enthusiasm for learning of their students. The closest example for their children is their parents; they imitate what they see. Therefore parents must always show a positive attitude in front of their children. Thus learning also requires guidance from parents so that mature attitudes and learning responsibilities grow in children. Parents who are more concerned with their work means that children do not get supervision/guidance from parents, but have an impact on children, so they experience learning difficulties.